2016
DOI: 10.1158/1078-0432.ccr-15-2879
|View full text |Cite
|
Sign up to set email alerts
|

Immune and Stromal Classification of Colorectal Cancer Is Associated with Molecular Subtypes and Relevant for Precision Immunotherapy

Abstract: Purpose: The tumor microenvironment is formed by many distinct and interacting cell populations, and its composition may predict patients' prognosis and response to therapies. Colorectal cancer is a heterogeneous disease in which immune classifications and four consensus molecular subgroups (CMS) have been described. Our aim was to integrate the composition of the tumor microenvironment with the consensus molecular classification of colorectal cancer.Experimental Design: We retrospectively analyzed the composi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
408
3
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 474 publications
(450 citation statements)
references
References 43 publications
30
408
3
9
Order By: Relevance
“…Se ha descrito como lesión precursora a los pólipos sésiles aserrados 36 . Estos tumores presentan una alta respuesta de infiltrado intratumoral, lo cual confiere a estos pacientes un buen pronós-tico y, según lo reportado, se sugiere que ello se debería a la presencia de linfocitos T citotóxicos CD8+ [37][38][39][40] . Por otra parte, se ha establecido que la mutación activante en el oncogen BRAF (V600E) provoca la activación constitutiva de la vía EGFR y en consecuencia una ineficiente respuesta al tratamiento con cetuximab o panitumumab.…”
Section: Discussionunclassified
“…Se ha descrito como lesión precursora a los pólipos sésiles aserrados 36 . Estos tumores presentan una alta respuesta de infiltrado intratumoral, lo cual confiere a estos pacientes un buen pronós-tico y, según lo reportado, se sugiere que ello se debería a la presencia de linfocitos T citotóxicos CD8+ [37][38][39][40] . Por otra parte, se ha establecido que la mutación activante en el oncogen BRAF (V600E) provoca la activación constitutiva de la vía EGFR y en consecuencia una ineficiente respuesta al tratamiento con cetuximab o panitumumab.…”
Section: Discussionunclassified
“…Recognizing that the tumor microenvironment is an important contributor to gene expression signals in bulk tumor tissue (24)(25)(26), the translation of CMS classification to preclinical models, including cell lines and patient-derived xenografts (PDX) has major challenges. Although CMS labels have previously been assigned to colorectal cancer cell lines (27), development of "adapted" CMS classifiers carefully optimized for preclinical exploration is critical to investigate specific drug sensitivities of subtypes in high-throughput screens.…”
Section: Introductionmentioning
confidence: 99%
“…High expression of lymphoid genes is associated with poor prognosis. Further analysis showed that this particular signature was associated with myeloid cells and fibroblasts with immunosuppressive mesenchymal markers (18) as well as a high proportion of endothelial cells and cancerassociated fibroblasts. This mesenchymal signature was identified as a marker of resistance in melanoma patients who did not respond to anti-PD-1 (19).…”
Section: Features Associated With Improved Immune Responsivenessmentioning
confidence: 97%
“…RNA expression profiling elucidated a T cell-rich signature present in both MSI-H and some MSS colorectal cancer patients who had a better prognosis (18). High expression of lymphoid genes is associated with poor prognosis.…”
Section: Features Associated With Improved Immune Responsivenessmentioning
confidence: 99%